2020
DOI: 10.1002/advs.202070017
|View full text |Cite
|
Sign up to set email alerts
|

Focal Brain Therapy: Transcranial Pulse Stimulation with Ultrasound in Alzheimer's Disease—A New Navigated Focal Brain Therapy (Adv. Sci. 3/2020)

Abstract: In article number 1902583, Roland Beisteiner and co‐workers describe a brain activation technique for treatment of Alzheimer's disease. Transcranial pulse stimulation (TPS) applies ultrashort ultrasound pulses to activate neuronal resources. A therapeutic breakthrough is secure clinical targeting and access to deep brain areas. After 2 weeks of treatment, memory performance improves for up to 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Functional MRI (fMRI) also showed significantly increased connectivity within the memory network ( 28). Beisteiner's study also found that participants' depressive symptoms were significantly improved as measured by Geriatric Depression Scale (GDS) (p = 0.005) and Beck Depression Inventory (BDI) (p < 0.0001) at 1-and 3-months post-stimulation follow-up compared with the baseline scores (28). Increased connectivity in memory network was also evident in Beisteiner's study (60) in the 3months post-stimulation follow-up.…”
Section: Previous Study By the Research Teammentioning
confidence: 81%
See 1 more Smart Citation
“…Functional MRI (fMRI) also showed significantly increased connectivity within the memory network ( 28). Beisteiner's study also found that participants' depressive symptoms were significantly improved as measured by Geriatric Depression Scale (GDS) (p = 0.005) and Beck Depression Inventory (BDI) (p < 0.0001) at 1-and 3-months post-stimulation follow-up compared with the baseline scores (28). Increased connectivity in memory network was also evident in Beisteiner's study (60) in the 3months post-stimulation follow-up.…”
Section: Previous Study By the Research Teammentioning
confidence: 81%
“…The recent development of a new NIBS called "transcranial pulse stimulation" (TPS) has been proven effective for only a 2-week treatment of 35 patients with Alzheimer's disease (AD). Patients' memories had shown improvement which lasted up to 3 months (28). However, there is a paucity of scientific evidence on the efficacy of this TPS intervention on other vulnerable psychiatric populations such as MDD, which is increasingly prevalent in Hong Kong and nationwide, especially during the COVID-19 pandemic (1,2,12,29).…”
Section: Non-invasive Treatment In Psychiatrymentioning
confidence: 99%